Pengaruh Persepsi Dukungan Organisasi Dan Keterikatan Kerja Terhadap Perilaku Inovatif Karyawan BPJS Kesehatan Cabang Magelang - Rieka Estuningtyas; Nur Wening (Jurnal Manajemen Kreatif dan Inovasi, 2024)
Achieving organizational targets is a major goal in an organization, including BPJS Health. With changing conditions towards digitalization, innovative behavior by employees is very necessary to make it easier to complete work. Organizational support in the form of attention and concern is an important factor in realizing innovative employee behavior. Another factor that also greatly influences employee innovative behavior is work engagement, where with this engagement employees will have passion for their work. This research aims to determine the influence of these two variables on employee innovative behavior. The method and analysis used in the research is a quantitative method with multiple regression analysis. The data collection technique used was a questionnaire to all permanent and contract employees at BPJS Health Magelang Branch with a total of 65 respondents. The results of this research show that first, there is a significant and positive influence of perceived organizational support on employee innovative behavior as evidenced by the t value of 3.357 and a significance of 0.001. Second, work engagement has a significant and positive influence on employee innovative behavior as evidenced by the t value of 5.605 and a significance of 0.000. Third, from the results of calculating the coefficient of determination it can be concluded that perceptions of organizational support and work engagement together have an influence on employee innovative behavior by 53%.